2021
DOI: 10.1186/s12909-021-02515-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of performance on the pediatric board certification examination

Abstract: Background Examining the predictors of summative assessment performance is important for improving educational programs and structuring appropriate learning environments for trainees. However, predictors of certification examination performance in pediatric postgraduate education have not been comprehensively investigated in Japan. Methods The Pediatric Board Examination database in Japan, which includes 1578 postgraduate trainees from 2015 to 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…During the course, all the trainees were supervised by the instructors and the course director, possibly resulting in an overestimation of their self-assessment on the post-training survey. Therefore, as the next step, implementing an instructor training course to maintain the quality of teaching skills at a high level and planning a longer course in pediatric POCUS use that includes objective measures, such as an objective structured clinical examination (OSCE), computer-based tests, and a control group, may be desirable to evaluate trainees' skills more accurately [30].…”
Section: Discussionmentioning
confidence: 99%
“…During the course, all the trainees were supervised by the instructors and the course director, possibly resulting in an overestimation of their self-assessment on the post-training survey. Therefore, as the next step, implementing an instructor training course to maintain the quality of teaching skills at a high level and planning a longer course in pediatric POCUS use that includes objective measures, such as an objective structured clinical examination (OSCE), computer-based tests, and a control group, may be desirable to evaluate trainees' skills more accurately [30].…”
Section: Discussionmentioning
confidence: 99%
“…The Jpem-SCT is designed to assess clinical reasoning skills among pediatric emergency medicine specialists, and its target examinees are pediatric and emergency medicine residents and pediatric emergency medicine fellows in Japan. In this context, the fact that being a transitional intern (PGY1 and 2) was a negative predictor of a good score (i.e., the questions were too difficult for early trainees) indicates the positive association between the subject's clinical reasoning ability (acquired through training and experience) and the Jpem-SCT score ( 16 ). This finding provides reasonable evidence on the ease of extrapolation of the Jpem-SCT to other assessment settings.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship has become increasingly important in postgraduate medical education 1–4 . The core competencies for residents include scholarship, 1,2,5 and trainees themselves have reported a desire for and satisfaction from participation in scholarly activities 4,6–10 .…”
Section: Introductionmentioning
confidence: 99%
“…
Scholarship has become increasingly important in postgraduate medical education. [1][2][3][4] The core competencies for residents include scholarship, 1,2,5 and trainees themselves have reported a desire for and satisfaction from participation in scholarly activities. 4,[6][7][8][9][10] However, it has been reported that scholarly activities, particularly article publication, were scarce in pediatrics residency training in Japan.
…”
mentioning
confidence: 99%